Transsexuality: Reconciling Christianity and Science - Fehige, Joerg H. Y. (Toronto journal of theology, 2011)
Furthering the dialogue with J. Wentzel van Huyssteen over his way of reconciling Christianity and science while reflecting on human uniqueness, I offer a philosophical analysis of the phenomenon of transsexuality. The focus of my analysis is the implications of transsexuality for the metaphysics of reductive naturalism. Envisioning a pluralistic ontology of the sexed human body, I propose to account for human sexuality within the general framework of normative pragmatism. The context of my reflections is a theology of sexual diversity, which I believe van Huyssteen has good reasons to endorse.